Diagnostic Ideas and Management Strategies for Thrombocytopenia of Unknown Causes in Pregnancy - Li, Jie; Gao, Yue-Hua; Su, Jing; Zhang, Lu; Sun, Yan; Li, Zeng-Yan (Frontiers in Surgery, 2022)
Objective: To summarize the clinical characteristics and treatment options together with the maternal and neonatal prognoses in women with different degrees of thrombocytopenia of unknown causes during pregnancy. Materials and methods: One hundred twenty-nine cases meeting the inclusion and exclusion criteria were retrospectively analyzed. Patients were divided into group A (50*109/L) and group B (50*109/L to 100*109/L) according to the lowest level of platelet count during pregnancy. Patients were divided into those found to have thrombocytopenia in the relatively early, middle, and late stages according to the detection period of maternal thrombocytopenia during pregnancy. Results: There were 72 cases in group A, and 57 cases in group B. There existed statistically significant differences in terms of the proportion of primipara, the proportion with a history of thrombocytopenia, and the median length of pregnancy between the two groups (p < 0.05). The proportion of patients with severe thrombocytopenia as an indication for cesarean delivery was higher in group A than in group B (p < 0.05). More cases were detected at the relatively early stages of pregnancy in group A than in group B (p < 0.05). There was no difference in neonatal hemorrhage and events of thrombocytopenia between the two groups. Conclusion: Patients with platelet counts below 50*109/L were mostly primipara with a history of thrombocytopenia, most often detected at a relatively early stage of pregnancy, and continued pregnancy might lead to aggravation of the disease. Combination therapy was required for patients with platelet counts below 30*109/L to maintain the platelet counts within a safe range. Cesarean delivery was selected to terminate the pregnancies, and platelet counts should be raised above 50*109/L before surgery. Close monitoring was required for those with platelet counts above 30*109/L. There was no direct correlation between the maternal and neonatal platelet counts.